2014
DOI: 10.1007/s00424-014-1554-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis-associated factors underlie the magnitude of response to aerobic endurance training in rats

Abstract: Trainability is important in elite sport and in recreational physical activity and the wide range for response to training is largely dependent on genotype. In this study, we compare a newly developed rat model system selectively bred for low and high gain in running distance from aerobic training to test whether genetic segregation for trainability associates with differences in factors associated with mitochondrial biogenesis. Low response trainer (LRT) and high response trainer (HRT) rats from generation 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 41 publications
1
39
0
1
Order By: Relevance
“…We and others have shown that exercise increases the activity and content of SIRT1 (Hart et al 2014;Kang et al 2013;Koltai et al 2011;Marton et al 2015;Radak et al 2011;Suwa et al 2008), while aging decreases NAD levels and NAMPT concentration (Koltai et al 2010). Moreover, it has also been reported that exercise training can attenuate the age associated decline in NAD and NAMT levels in skeletal muscle of rats (Koltai et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that exercise increases the activity and content of SIRT1 (Hart et al 2014;Kang et al 2013;Koltai et al 2011;Marton et al 2015;Radak et al 2011;Suwa et al 2008), while aging decreases NAD levels and NAMPT concentration (Koltai et al 2010). Moreover, it has also been reported that exercise training can attenuate the age associated decline in NAD and NAMT levels in skeletal muscle of rats (Koltai et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a variety of biochemical, cellular, and systemic adaptations that occur in response to exercise that are intimately linked to redox control (Baar, 2014;Marton et al, 2014). ROS increase during and following exercise (Davies et al, 1982; Alessio and Goldfarb, 1988;Radak et al, 2001).…”
Section: Exercise and Lifestyle Modification In Ckdmentioning
confidence: 99%
“…Mitochondrial biogenesis is a consistent adaptation to exercise, and seems to contribute to the majority of gained benefits to systemic redox control (Baar et al, 2002; Koltai et al, 2012;Marton et al, 2014). Mitochondrial biogenesis is presumed to occur due to increased reliance on aerobic metabolism, and is initiated by increased ROS signalling (Kang et al, 2009).…”
Section: Exercise and Lifestyle Modification In Ckdmentioning
confidence: 99%
See 2 more Smart Citations